The FRZB gene regulates hair follicle development in rabbits via the Wnt/β-catenin signaling pathway - Fan Wang; Xiyu Zhang; Yingying Dai; Bohao Zhao; Xinsheng Wu; Yang Chen (World Rabbit Science, 2023)
To explore the mechanism of the FRZB gene in hair follicle development by regulating the Wnt/β-catenin signalling pathway, Angora rabbits were selected to collect back skin samples for the experiment. The action mechanism is understood by cell culture and transfection, apoptosis and proliferation assays and TOP/FOP Flash Wnt Reporting System methods. The results showed that the interference and overexpression of the FRZB gene in rabbit dermal papilla cells indicated that overexpression could inhibit the expression of SFRP2, BMP4, and WNT2 genes (P<0.05). On the contrary, the expression of Wnt signalling pathway-related genes LEF1, CCND1, DKK1, and TCF7 was significantly up-regulated (P < 0.05). Further examination of the luciferase reporter system TOP/FOP revealed that pcDNA3.1-FRZB inhibits Wnt activity. PcDNA3.1-FRZB was found to promote the level of apoptosis in DP cells, whereas si-FRZB inhibited DP cell proliferation. Therefore, it is concluded that FRZB inhibits hair follicle development in long-haired rabbits by regulating the Wnt/β-catenin signalling pathway.